REGISTERS USED BY MULTI LEVEL MARKETING BUSINESS MEMBERS IN PT. ORINDO ALAM AYU - UMAMI, RISA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords : Sociolinguistics, Register, Multi Level Marketing, PT. Orindo Alam Ayu, The Great One Club. Humans live together as society and the social creature. Humans need alanguage for communicating with each other in their live. People create group ofsocieties based on region, interest, social class, religion and many others. Inspecific group people create their own terms in their community and it is calledregister. In this study, the writer conducted a study about register used by multilevel marketing business members in PT. Orindo Alam Ayu. There are twoproblems of the study, they are (1) What are the registers used by the members of multi level marketing business in PT. Orindo Alam Ayu?; (2) What are thecontextual factors influencing the registers used by members of multi levelmarketing business in PT. Orindo Alam Ayu?In this study, the writer used descriptive qualitative approach with homogeneous purposive sampling. The data were conversation between the members and the data source was two small meetings of The Great One Club in PT. Orindo Alam Ayu discussing success plan knowledge and recruiting strategy (new recruitment program start from November) topics. The writer described the contextual analysis of the conversation where the registers used by the members.The writer found 22 registers used by the members of multi level maketingin PT. Orindo Alam Ayu. Some of the registers have common sense but some donot. Then, some registers in carrier levels of PT. Orindo Alam Ayu have analogywith the precious things, such as Gold Executive Director, Sapphire ExecutiveDirector, and Diamond Executive Director. Carrier levels are made based on thevaluable levels of gold, sapphire, and diamond. Diamond has the highest value so it is always at the top of the levels after gold and sapphire. Then, there are seven registers in acronym form such as OOM, BC, WP, and SPO. In contextual factor analysis, generally the writer found most of the contextual factors influencing the speakers are about carrier levels and ordering system. The situation is when the member share information in purpose to make the other members fell enthusiastic to attain next level and the discursive functions always support the topics and the social roles or the situations.The registers used by Multi Level Marketing Business members in PT. Orindo Alam Ayu had relation with the selling system and the carrier level and ordering system in their business. Those registers are important knowledge to reach success in the business. The writer suggested for the next writer to analyzeregister in other business community because business field is the interestingsubject. It can give information, not only for English students but also for otherpeople who need business information.